20‐3: Novel Host‐Guest System for Drastic Improvement in the Lifetime of a Deep‐Red OLED that Satisfies the Red Chromaticity of the BT.2020 Standard. Issue 1 (30th May 2018) - Kido, Hiromitsu; Yamaguchi, Tomoya; Inoue, Hideko; Sasaki, Toshiki; Ohsawa, Nobuharu; Seo, Satoshi; Yamazaki, Shunpei
Abstract : We developed a novel host‐guest system that increases the lifetime of a deep‐red phosphorescent OLED covering the wide color gamut of the BT.2020 standard. An OLED that employs this host‐guest system has a ~5.4 times longer lifetime than an OLED that employs the conventional system.